Global Qibla Direction Using Stellar Transit at Kaaba Latitude - Fathurrahman, Fathurrahman; Fuscha, Fika Afhamul (Fakultas Syari'ah dan Hukum UIN Walisongo, 2025)
The global rashd al-qiblah is currently considered the most accurate and easily applicable method for measuring the qibla direction, as it utilizes the sun’s shadow during its transit above the Kaaba. Unfortunately, this event occurs only twice a year, and the sun's disk diameter of 0.5° reduces the accuracy of the method. The global rashd al-qiblah method, which utilizes stars with declinations equal to the latitude of the Kaaba, with its higher annual frequency and point-sized stellar disks, is more effective to use. This study employs a library research method with a qualitative and multidisciplinary approach, integrating both religious science and natural science. This study aims to develop an alternative method for determining the global qibla direction using stellar transit. Thirty-two stars can be utilized for the worldwide star rashd al-qiblah method, each usable for measurements over approximately 177.41 days. This means the global rashd al-qiblah method can be applied approximately 2,838 times across multiple countries within one year.